STRATEGY FOR IMPROVING PURCHASING POWER OF PEOPLE THROUGH SCIENCE AND TECHNOLOGY FOR THE FARMERS ROSELA - Diah, Mardiah (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2017)
The increase in revenues is one way to increase purchasing power. This community activities aimed to increase the income of farmers through improving the knowledge of farmers. This can be done by improving knowledge about the quality of the product, packaging of product, management of bookkeeping, and marketing . Evaluation of these activities be done by monitoring all activities of product producing and marketing and seek information about the problem that happened as long as periode this activities.